Pengelolaan kelas dalam perspektif manajemen mutu terpadu di SMP 4 Semin Gunungkidul - Heri Miswanto; Samsi Haryanto (Universitas Sarjanawiyata Tamansiswa, 2016)
The purposes of the research are to get clear descriptions of (1) the planning of classroom management, 2) the organizing classroom management, 3) the implementation of classroom management, 4) the conducting of classroom management, 5) the evaluation of the results of classroom management, 6) the efforts of the increasing of classroom management quality, and 7) the relationship between classroom management and the integrated Quality Management in SMP N 4 Semin Gunungkidul. The research method used is the descriptive qualitative approach; the choice of research resource persons is by using purposive sampling technique. In this research, the headmistress, teachers, office staff, students, school committees, students’ parents, and community as resources. The instrument in this research is the researcher himself as the key instrument. The data is collected by using interview, observation, and document review. The data were analyzed inductively, the analysis of data activity they are reduction data, the display data and conclusion drawing/verification. The results of this study have found several facts: first, the pattern of classroom management in SMP N 4 Semin Gunungkidul is like the perspective of Total Quality Management (TQM) in the school improvement and be able to answer the needs of learners because the learning models oriented focus in customer satisfaction those are students. Second, the classroom management in SMP N 4 Semin Gunungkidul in terms of planning , organizing, implementing , monitoring and evaluation , supervising and controlling the efforts of improving the quality in good and excellent categories, because the classroom management needs all components of the school related to integration of management quality to reach the goal effectively and efficiently, while the integrated quality management to produce the quality according to the demands of society (customer satisfaction).